Sensations of history animation and new media art - Hodge, James J. (Electronic Mediations, Vol. 57, 2019)
A phenomenological investigation into new media artwork and its relationship to history What does it mean to live in an era of emerging digital technologies? Are computers really as antihistorical as they often seem?